Tumescent Anethesia : A Useful Technique For Harvesting Split- Thickness Skin Graft - Saraf Sanjay; Goyal Prashant; Ranka Pankaj (Wolters Kluwer Medknow Publications, 2004)
Tumescent anesthesia is a now an established technique for regional anesthesia of the skin and the subcutaneous fatty tissue. The unsurpassed simplicity and safely of this procedure have opened up the gates for newer indications. We have employed this technique for harvesting split-thickness grafts in various conditions. We have found that this technique is extremely simple in which large areas can be anesthetized for harvesting split-thickness skin grafts safely. The good passive resistance achieved facilitates easy harvesting of split-thickness grafts along with minimal bleeding and long lasting pain relief. We found this to be an inexpensive, safe and simple technique with elimination of risks and expenses of general anesthesia.